Ending the Global Kleptocracy: Financial Innovation for the 21st Century - Priels, Koenraad (University of Darussalam Gontor Press, 2023)
The purpose of this paper is to present a comprehensive and workable answer for addressing the socio-ecological crises that result from the severely flawed socio-economic system that is the capitalist world system to date. It presents a fundamental first step towards correcting this system, by addressing and correcting the monetary system whereupon a global kleptocracy has been constructed. At this point, there are no more excuses for social scientists, politicians, and regulatory agencies to hide in ivory towers. Conclusively, the feasible possibility for a pro-social, pro-ecological, and pro-economical financial system is presented here